PENGARUH PENGGUNAAN METODE PEMBELAJARAN SQ3R TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN DI SEKOLAH DASAR - Putri, Yudha Eka; Halidjah, Siti; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze whether there was influence of application of learning method of SQ3R (Survey, Question, Read, Recite, Review) to reading comprehension skill of IVB class student of northern pontianak elementary school. The method used was experimental method, while the research used pre-experimental design with one-group pretest-posttest design. Population and sample in this research was all student of class of IVB Primary School of State 33 northern Pontianak of amounted to 34 student. Data collection techniques used in this study were the technique of measurement techniques. The research instrument used was reading skill test. Based on result of data analysis from mean value pre-test 53,29 and average post-test 69,94. T test result obtained  = 5%, with db = 33 was 1,69. Because  (12,24)>  (1,69), so alternative hypothesis (Ha) accepted, it can be concluded that there was influence of applying learning method of SQ3R (Survey, Question, Read, Recite, Review) class IVB Elementary School 33 northern Pontianak.  Keywords: Learning Method SQ3R, Reading Comprehension Skills